Сверхзвуковой флаттер панели умеренных размеров, нагруженной по двум направлениям: растянутой по потоку газа и сжатой в перпендикулярном направлении, при набегании потока на ее свободный край - Мартиросян, С. Р. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Supersonic flutter of a moderate sized panel loaded in two directions: stretched along the gas flow and compressed in the perpendicular direction, when the flow runs into its free edge. By analyzing, as an example, a thin elastic plate of a moderate sized, initially loaded in two directions: stretched along supersonic the gas flow and compressed in the perpendicular direction, we study the influence of the initial stress state of the plate on the stability of the unperturbed equilibrium state of the dynamical system “plate – flow” under the assumption that the flow runs into the free edge of the panel, on which there are concentrated inertial masses and moments. An analytical solution of the problem of stability is obtained. An accurate assessment of the influence of initially loading forces on the stability of the system is given. Ուսումնասիրված է գերձայնային գազի հոսքում մեկ ազատ եզրով ուղղանկյուն սալի նախնական լարվածային վիճակի ազդեցությունը, պայմանավորված ձգված շրջհոսման ուղղությամբ և միաժամանակ սեղմված ուղղահայաց ուղղությամբ ուժերով, «սալ–հոսք» դինամիկ համակարգի ոչխոտորված հավասարակշռության վիճակի կայունության վրա: Ենթադրվում է, որ սալի ազատ եզրին առկա են կենտրոնացած իներցիոն զանգվածներ և մոմենտներ: Ստացված է կայունության խնդրի անալիտիկ լուծումը: «Սալ–հոսք» համակարգի կայունության վրա նախնական ուժերի ազդեցությանը տրված է խիստ գնահատական:
Keywords: Механика